Pectoralis major flap for pharyngocutaneous fistula after total laryngectomy – two different approaches - Kovačević, Toma; Milisavljević, Natalija; Kovačević, Tatjana (Vojnosanitetski pregled, 2023)
Introduction. The reconstruction of large postoperative defects after oncologic surgery of the head and neck remains challenging. Regional flaps are considered a less expensive reconstructive option compared to free flaps. The pectoralis major flap is one of the most versatile choices for the reconstruction of large head and neck defects. Case report. We present technical key points for safe harvesting of pectoralis major flap for two cases in a university-affiliated tertiary care medical center. Both patients were male, with an average age of 64 years. The defects that required reconstruction in Case 1 were on the lateral neck region and, in Case 2, on the anterior side of the neck. Flaps were used for covering the pharyngocutaneous fistula after total laryngectomy and irradiation. The donor site was closed primarily. Flaps in both patients healed primarily without complications. Conclusion. The pectoralis major flap has a constant vascular pedicle and can successfully be used for the reconstruction of large head and neck defects. In order to obtain absolute flap survival, the operative technique must be impeccable.
Keywords: fistula; head and neck neoplasms; laryngectomy; pharynx; plastic surgery procedures; surgical flaps